SEAFLOOR FAULTING AND ITS RELATION TO SUBMARINE VOLCANIC ACTIVITIES BASED ON SUB BOTTOM PROFILING (SBP) ANALYSES IN WEH ISLAND WATERS AND ITS SURROUNDING, NANGROE ACEH DARUSSALAM PROVINCE - Hananto Kurnio; Ildrem Syafri; Adjat Sudradjat; Mega Fatimah Rosana; Dicky Muslim (BULLETIN OF THE MARINE GEOLOGY, 2015)
Sub bottom Profiling survey using strata box, a specially designed low penetration sub bottom Profiling (< 80 m) for coastal waters exploration, found out evidence of submarine volcanic activities in northern coastal waters of Weh Island, NanggroeAceh Darussalam Province. Gas bubbling could be observed at water columns of the digital sub bottom Profiling records as acoustic turbidity. There are at least 33 spots of volcanic gas bursts observed from the sub bottom Profiling. Examination of gas bursts at coastal area which show fumaroles and solfatara indicate reduce volcanic activity either at submarine or terrestrial. Identification of seafloor gas burst by diving team found out that center of such burst is occurred at a north - south opened lineation assumed as normal fault. It seems that the seafloor normal fault is the continuation of terrestrial fault of the same direction as observed from terrain earth google of Weh Island.Keywords: seafloor faulting, submarine volcanic activities, shallow sub bottom Profiling data, Weh Island Aceh Survei penampang bawah dasar laut (SBP) menggunakan strata box, suatu alat SBP penetrasi rendah yang didisain untuk eksplorasi perairan pantai, mendapatkan bukti-bukti aktivitas gunungapi bawah laut di perairan sebelah utara Pulau Weh, Provinsi Nanggroe Aceh Darussalam. Gelembung-gelembung gas dapat diamati pada kolom air rekaman digital penampang bawah dasar laut sebagai turbiditas akustik. Sedikitnya dijumpai 33 titik semburan gas volkanik yang teramati dari penampang bawah dasar laut tersebut. Pemeriksaan semburan-semburan gas pada wilayah pantai sebagai fumarola dan solfataramenunjukkan telah berkurangnya aktivitas volkanik apakah pada dasar laut maupun darat. Identifikasi semburan gas dasar laut oleh tim selam mendapatkan bahwa pusat semburan berada pada kelurusan berarah utara - selatan yang diduga sebagai sesar normal. Tampaknya adalah bahwa sesar normal dasar laut tersebut merupakan kelanjutan sesar darat yang berorientasi sama seperti teramati dari citra earthgoogle terrain Pulau Weh. Kata kunci: pensesaran dasar laut, aktivitas gunungapi bawah laut, data penampang bawah dasar laut, Pulau Weh Aceh